Magnesium-manganese-aluminum composite spinel refractory material and preparation method thereof

By preparing magnesium-manganese-aluminum composite spinel refractory materials, and utilizing specific raw materials and processes, the problems of high thermal conductivity, low strength, and insufficient corrosion resistance of magnesium-manganese-aluminum spinel refractory materials in high-temperature industrial fields have been solved, achieving high strength, low thermal conductivity, and excellent kiln coating performance of the material.

CN120965303AActive Publication Date: 2025-11-18MARVELS REFRACTORIES ANSHAN CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511500066.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2025-11-18
Estimated Expiration
2045-10-21

AI Technical Summary

Technical Problem

Existing magnesium manganese aluminum spinel refractory materials suffer from problems such as high thermal conductivity, low strength, insufficient kiln coating performance, and inadequate corrosion resistance in high-temperature industrial applications.

Method used

Magnesium-manganese-aluminum composite spinel refractory materials are prepared by mixing, molding and sintering raw materials such as magnesia, iron-aluminum spinel, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, binder, nano-zirconia and nano-titanium oxide, calcium hexaaluminate and titanium dioxide-coated aluminosilicate fibers. The additives and calcium hexaaluminate work synergistically to reduce the thermal conductivity, and the fibers improve the strength and corrosion resistance.

Benefits of technology

It significantly reduces thermal conductivity, improves the strength and corrosion resistance of refractory materials, enhances the performance of kiln lining, and meets the requirements of high-temperature industrial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a magnesium-manganese-aluminum composite spinel refractory material and a preparation method thereof, and belongs to the technical field of refractory materials. The magnesium-manganese-aluminum composite spinel refractory material provided by the invention is prepared from the following raw materials in parts by mass: 40 to 120 parts of magnesia, 1 to 20 parts of hercynite, 1 to 5 parts of alpha-Al2O3 micro powder, 0.1 to 2 parts of manganese dioxide powder, 0.1 to 2 parts of manganese powder, 1 to 5 parts of binding agent, 0.1 to 1 part of additive, 10 to 20 parts of calcium hexaluminate and 5 to 15 parts of fiber, the fibers are titanium dioxide coated aluminum silicate fibers; the additives are nano zirconium oxide and nano titanium oxide. The additive and calcium hexaluminate in the invention can synergistically reduce the heat conductivity coefficient; the fibers have lower heat conductivity coefficient, so that the internal structure of the refractory material is tighter, and the strength is obviously improved; the aluminum silicate fiber has excellent thermal stability and chemical stability, and can improve the kiln coating hanging performance and the corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of refractory materials, and particularly relates to a magnesium-manganese-aluminum composite spinel refractory material and a preparation method thereof. BACKGROUND

[0002] The magnesium-manganese-aluminum spinel refractory material is a high-performance refractory material mainly formed of oxides of magnesium, manganese and aluminum in a spinel structure. The material is widely used in cement kilns, steel smelting and other high-temperature industrial fields due to its excellent high-temperature performance and thermal shock resistance. However, with the development of the industrial field, the current magnesium-manganese-aluminum spinel refractory material cannot meet the use requirements, and has problems of high thermal conductivity, low strength, low kiln skin hanging performance and low corrosion resistance. Therefore, how to reduce the thermal conductivity of the magnesium-manganese-aluminum spinel refractory material and improve the strength, kiln skin hanging performance and corrosion resistance has become a difficult problem to be solved in the field. SUMMARY

[0003] The application aims to provide a magnesium-manganese-aluminum composite spinel refractory material and a preparation method thereof. The magnesium-manganese-aluminum composite spinel refractory material provided by the application has excellent strength, kiln skin hanging performance, corrosion resistance and low thermal conductivity.

[0004] In order to achieve the above application purposes, the application provides the following technical solutions: The application provides a magnesium-manganese-aluminum composite spinel refractory material prepared from raw materials including the following mass fractions: 40-120 parts of magnesite, 1-20 parts of hercynite, 1-5 parts of alpha-Al2O3 micro powder, 0.1-2 parts of manganese dioxide powder, 0.1-2 parts of manganese powder, 1-5 parts of a binding agent, 0.1-1 part of an additive, 10-20 parts of calcium hexaluminate and 5-15 parts of fiber; The fiber is titanium dioxide-coated aluminum silicate fiber. The additive is nano zirconium oxide and nano titanium oxide.

[0005] Preferably, the magnesium-manganese-aluminum composite spinel refractory material is prepared from raw materials including the following mass percentages: 50-100 parts of magnesite, 5-15 parts of hercynite, 2-4 parts of alpha-Al2O3 micro powder, 0.5-1.5 parts of manganese dioxide powder, 0.5-1.5 parts of manganese powder, 2-4 parts of a binding agent, 0.2-0.9 part of an additive, 12-18 parts of calcium hexaluminate and 8-12 parts of fiber.

[0006] Preferably, the mass ratio of the nano zirconium oxide and the nano titanium oxide is 1: (1-5).

[0007] Preferably, the particle size of the alpha-Al2O3 micro powder is 400-600 mesh.

[0008] Preferably, the particle size of the manganese dioxide powder is 300-500 mesh.

[0009] Preferably, the mass ratio of the additive and calcium hexaluminate is 1: (10-20).

[0010] Preferably, the mass ratio of the additive and calcium hexaluminate is 1: (14-16).

[0011] The application also provides a preparation method of the magnesium-manganese-aluminum composite spinel refractory material, comprising the following steps: (1) mixing magnesite, hercynite, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, a binder, an additive, calcium hexaluminate and fibers to obtain a mixture; (2) forming the mixture obtained in step (1) to obtain a green body; (3) sintering the green body obtained in step (2) to obtain the magnesium-manganese-aluminum composite spinel refractory material.

[0012] Preferably, the pressure for forming in step (2) is 10-15 kN / cm 2 .

[0013] Preferably, the sintering temperature in step (3) is 1000-1300℃, and the sintering time is 5-12 h.

[0014] The application provides a magnesium-manganese-aluminum composite spinel refractory material, which is prepared from raw materials including the following components in mass fraction: 40-120 parts of magnesite, 1-20 parts of hercynite, 1-5 parts of α-Al2O3 micro powder, 0.1-2 parts of manganese dioxide powder, 0.1-2 parts of manganese powder, 1-5 parts of a binder, 0.1-1 part of an additive, 10-20 parts of calcium hexaluminate and 5-15 parts of fibers; the fibers are titanium dioxide-coated aluminum silicate fibers; and the additive is nano zirconium oxide and nano titanium oxide. The additive and calcium hexaluminate in the application can synergistically reduce the thermal conductivity; the additive can accelerate the diffusion of the crystal boundary and seal the pores in the crystal grains, thereby reducing the thermal conductivity; the calcium hexaluminate has a low thermal conductivity and excellent chemical corrosion resistance, which can effectively improve the corrosion resistance and reduce the thermal conductivity; the fibers have a low thermal conductivity, which can reduce the thermal conductivity; as a sintering aid, the fibers can promote the sintering of the spinel, make the internal structure of the refractory material more compact and significantly improve the strength; in addition, the aluminum silicate fibers have excellent thermal stability and chemical stability, which can improve the hanging kiln skin performance and corrosion resistance. Experimental results show that the bulk density of the magnesium-manganese-aluminum composite spinel refractory material provided by the application is 2.98-3.00 g / cm 3The apparent porosity is 15.3-16.2%, the normal-temperature compressive strength is 65-75 MPa, the thermal conductivity (1000 DEG C) is 2.439-2.840 W / m*K, the corrosion resistance is 12-18%, and the hanging kiln skin performance is 20.54-25.09 MPa. DETAILED DESCRIPTION

[0015] The application provides a magnesium-manganese-aluminum composite spinel refractory material, which is prepared from raw materials including the following components in parts by mass: 40-120 parts of magnesia, 1-20 parts of hercynite, 1-5 parts of alpha-Al2O3 micro powder, 0.1-2 parts of manganese dioxide powder, 0.1-2 parts of manganese powder, 1-5 parts of a binding agent, 0.1-1 part of an additive, 10-20 parts of calcium hexaluminate and 5-15 parts of fibers; The fibers are titanium dioxide-coated aluminum silicate fibers. The additive is nano zirconium oxide and nano titanium oxide.

[0016] The application does not have special limitations on the sources of the raw materials, and commercially available products known to those skilled in the art can be used.

[0017] The raw materials for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the application include 40-120 parts of magnesia in parts by mass. As an embodiment, the magnesia can be 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts or 110 parts in mass. In the application, the content of magnesia is controlled to cooperate with other components, so that the mineral stability and volume stability of the refractory material are ensured, and the mechanical flexibility of the refractory material is improved.

[0018] In the application, the magnesia preferably includes magnesia particles and magnesia fine powder; the particle size of the magnesia particles is preferably 3-5 mm; the particle size of the magnesia fine powder is preferably less than 0.063 mm; and the mass ratio of the magnesia particles to the magnesia fine powder is preferably (1-5):1. In the application, the content of magnesia is controlled to cooperate with other components, so that the mineral stability and volume stability of the refractory material are ensured, and the mechanical flexibility of the refractory material is improved; the mass ratio of the magnesia particles to the magnesia fine powder is controlled, so that the compressive strength of the refractory material is further improved; the magnesia particles serve as a framework, and the magnesia fine powder fills the gaps, so that the compactness of the refractory material is improved, and the compressive strength of the refractory material is improved.

[0019] As an embodiment, the mass ratio of the magnesia particles to the magnesia fine powder can be 2:1, 3:1 or 4:1.

[0020] In the application, the magnesia preferably includes fused magnesia and / or sintered magnesia; and the mass percentage content of MgO in the magnesia is preferably greater than or equal to 96%.

[0021] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the present application includes 1-20 parts of hercynite, in terms of 40-120 parts of magnesia. As an embodiment, the mass fraction of the hercynite can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts or 19 parts. In the present application, the iron ions in the hercynite diffuse into the magnesia, improving the hanging kiln skin performance of the refractory material; in addition, the hercynite can also react with the magnesia, thereby improving the strength of the refractory material.

[0022] In the present application, the particle size of the hercynite is preferably 1-3 mm.

[0023] As an embodiment, the chemical composition of the hercynite can include Fe2O340.22%, SiO21.32%, Al2O355.81% and CaO 2.65%, in terms of mass percentage.

[0024] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the present application includes 1-5 parts of α-Al2O3 micro powder, in terms of 40-120 parts of magnesia. As an embodiment, the mass fraction of the α-Al2O3 micro powder can be 2 parts, 3 parts or 4 parts. In the present application, the α-Al2O3 micro powder can promote sintering, thereby improving the strength and hanging kiln skin performance of the refractory material.

[0025] In the present application, the particle size of the α-Al2O3 micro powder is preferably 400-600 mesh. As an embodiment, the particle size of the α-Al2O3 micro powder can be 500 mesh.

[0026] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the present application includes 0.1-2 parts of manganese dioxide powder, in terms of 40-120 parts of magnesia. As an embodiment, the mass fraction of the manganese dioxide powder can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts or 1.9 parts. In the present application, the manganese ions in the manganese dioxide powder form a stable structure during sintering, thereby providing the strength and hanging kiln skin performance of the refractory material.

[0027] In the present application, the particle size of the manganese dioxide powder is preferably 300-500 mesh. As an embodiment, the particle size of the manganese dioxide powder can be 400 mesh.

[0028] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the present application includes 0.1-2 parts of manganese powder, based on 40-120 parts of magnesia. As an embodiment, the manganese powder can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts or 1.9 parts in mass fraction. In the present application, the manganese powder forms a stable structure during sintering, thereby providing the strength and kiln skin adhesion of the refractory material.

[0029] In the present application, the particle size of the manganese powder is preferably 300-500 mesh. As an embodiment, the particle size of the manganese powder can be 400 mesh.

[0030] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the present application includes 1-5 parts of a binder, based on 40-120 parts of magnesia. As an embodiment, the binder can be 2 parts, 3 parts or 4 parts in mass fraction. In the present application, the binder can be directly volatilized during sintering and can ensure the initial strength after shaping.

[0031] In the present application, the binder preferably includes at least one of dextrin solution, calcium lignosulfonate solution, methyl cellulose solution and sulfite pulp waste liquid. The present application does not have special limitation on the concentration of the dextrin solution, calcium lignosulfonate solution, methyl cellulose solution and sulfite pulp waste liquid, and the concentration known to those skilled in the art can be used.

[0032] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the present application includes 0.1-1 parts of an additive, based on 40-120 parts of magnesia. As an embodiment, the additive can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or 0.9 parts in mass fraction. In the present application, the additive can accelerate the grain boundary diffusion and seal the pores inside the crystal grains, thereby reducing the thermal conductivity.

[0033] In the present application, the additive is nano-zirconium oxide and nano-titanium oxide; and the mass ratio of the nano-zirconium oxide to the nano-titanium oxide is preferably 1: (1-5). As an embodiment, the mass ratio of the nano-zirconium oxide to the nano-titanium oxide can be 1:2, 1:3 or 1:4. The present application can further reduce the thermal conductivity of the refractory material by controlling the mass ratio of the nano-zirconium oxide to the nano-titanium oxide.

[0034] In the present application, the additive has a D 50 The particle size is preferably 50-100 nm.

[0035] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the application comprises 10-20 parts of calcium hexaluminate, based on 40-120 parts of magnesia. As an embodiment, the mass fraction of the calcium hexaluminate can be 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts or 19 parts. In the application, the calcium hexaluminate has a low thermal conductivity and excellent chemical corrosion resistance, which can effectively improve the corrosion resistance and reduce the thermal conductivity.

[0036] As an embodiment, the content of CaO in the calcium hexaluminate can be 8-10 wt%, and the sphericity can be 0.8-0.85.

[0037] In the application, the particle size of the calcium hexaluminate is preferably 0.1-0.3 mm.

[0038] The raw material for preparing the magnesium-manganese-aluminum composite spinel refractory material provided by the application comprises 5-15 parts of fiber, based on 40-120 parts of magnesia. As an embodiment, the mass fraction of the fiber can be 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts. In the application, the fiber has a low thermal conductivity, which can reduce the thermal conductivity, and as a sintering aid, it can promote the sintering of spinel, making the internal structure of the refractory material more compact and the strength significantly improved.

[0039] In the application, the fiber is titanium dioxide-coated aluminum silicate fiber. In the application, the aluminum silicate fiber has excellent thermal stability and chemical stability, etc., which can improve the hanging kiln skin performance and corrosion resistance.

[0040] In the application, the mass ratio of the additive to the calcium hexaluminate is preferably 1:(10-20). As an embodiment, the mass ratio of the additive to the calcium hexaluminate can be 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18 or 1:19. By controlling the mass ratio of the additive to the calcium hexaluminate within the above range, the application can further reduce the thermal conductivity of the refractory material.

[0041] The additive and the calcium hexaluminate in the application can synergistically reduce the thermal conductivity; wherein the additive can accelerate the grain boundary diffusion, and close the pores inside the crystal grains, thereby reducing the thermal conductivity; the calcium hexaluminate has a low thermal conductivity and excellent chemical corrosion resistance, which can effectively improve the corrosion resistance and reduce the thermal conductivity; the fiber has a low thermal conductivity, which can reduce the thermal conductivity, and as a sintering aid, it can promote the sintering of spinel, making the internal structure of the refractory material more compact and the strength significantly improved; in addition, the aluminum silicate fiber has excellent thermal stability and chemical stability, etc., which can improve the hanging kiln skin performance and corrosion resistance.

[0042] The application further provides a preparation method of the magnesium-manganese-aluminum composite spinel refractory material. (1) mixing magnesite, hercynite, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, a binder, an additive, calcium hexaluminate and fibers to obtain a mixture; (2) forming the mixture obtained in the step (1) to obtain a blank; (3) sintering the blank obtained in the step (2) to obtain the magnesium-manganese-aluminum composite spinel refractory material.

[0043] The application mixes magnesite, hercynite, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, a binder, an additive, calcium hexaluminate and fibers to obtain a mixture.

[0044] The application does not have special limitations on the mixing of the magnesite, hercynite, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, a binder, an additive, calcium hexaluminate and fibers, and any preparation method known to those skilled in the art can be used.

[0045] After obtaining the mixture, the application forms the mixture to obtain a blank.

[0046] In the application, the forming pressure is preferably 10-15 kN / cm 2 . As an embodiment, the forming pressure can be 11 kN / cm 2 , 12 kN / cm 2 , 13 kN / cm 2 or 14 kN / cm 2 .

[0047] The application does not have special limitations on the forming time, as long as the forming can be completed.

[0048] After the forming is completed, the application preferably dries the product obtained by the forming to obtain a blank.

[0049] In the application, the drying temperature is preferably 120-250°C, and more preferably 150-200°C; and the drying time is preferably 48-72 h, and more preferably 55-60 h.

[0050] After obtaining the blank, the application sintering the blank to obtain the magnesium-manganese-aluminum composite spinel refractory material.

[0051] In the present application, the sintering temperature is preferably 1000-1300℃; the sintering time is preferably 5-12h. As an embodiment, the sintering temperature can be 1050℃, 1100℃, 1150℃, 1200℃ or 1250℃; the sintering time can be 6h, 7h, 8h, 9h, 10h or 11h. The present application can form stable microstructure and mineral phase by sintering.

[0052] The preparation method provided by the present application has simple process.

[0053] The technical solutions in the present application will be clearly and completely described below in combination with the embodiments in the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.

[0054] Embodiment 1 A magnesium-manganese-aluminum composite spinel refractory is prepared from the following raw materials in parts by mass: 40 parts of magnesite, 20 parts of hercynite, 1 part of α-Al2O3 micro powder, 2 parts of manganese dioxide powder, 0.1 part of manganese powder, 5 parts of binder, 1 part of additive, 20 parts of calcium hexaluminate and 5 parts of fiber; The magnesite is magnesite particles and magnesite fine powder; the particle size of the magnesite particles is 3-5mm; the particle size of the magnesite fine powder is below 0.063mm; the mass ratio of the magnesite particles to the magnesite fine powder is 1:1; The magnesite is fused magnesite; the mass percentage content of MgO in the magnesite is 96%; The particle size of the hercynite is 1-3mm; The chemical composition of the hercynite is Fe2O340.22%, SiO21.32%, Al2O355.81% and CaO 2.65% by mass percentage; The particle size of the α-Al2O3 micro powder is 500 mesh; The particle size of the manganese dioxide powder is 400 mesh; The particle size of the manganese powder is 300 mesh; The binder is calcium lignosulfonate solution, and the concentration of the calcium lignosulfonate solution is 1.23g / mL; The additive is nano zirconium oxide and nano titanium oxide; the mass ratio of the nano zirconium oxide to the nano titanium oxide is 1:2; The D50 of the additive is 50nm; 50 The particle size is 50nm; The content of CaO in the calcium hexaluminate is 8wt%, and the sphericity is 0.8. The particle size of the calcium hexaluminate is 0.1 mm; The fiber is titanium dioxide coated aluminum silicate fiber, and the preparation method is as follows: 0.05 L of tetrabutyl titanate is uniformly dispersed in 30 L of anhydrous ethanol, then 1 kg of aluminum silicate fiber is uniformly mixed, and then the solvent is evaporated to obtain the fiber; wherein the Al2O3 content in the aluminum silicate fiber is 65.07 wt%, the SiO2 content is 34.13 wt%, the diameter is 3 μm, and the length is 3 mm; The mass ratio of the additive to the calcium hexaluminate is 1:20; The preparation method of the magnesium-manganese-aluminum composite spinel refractory material is as follows: (1) magnesium sand, iron-aluminum spinel, α-Al2O3 powder, manganese dioxide powder, manganese powder, binder, additive, calcium hexaluminate, and fiber are mixed to obtain a mixture; (2) the mixture obtained in step (1) is formed under a pressure of 10 kN / cm2, and then dried at 150°C for 50 h to obtain a blank; 2 (3) the blank obtained in step (2) is sintered at 1200°C for 10 h to obtain a magnesium-manganese-aluminum composite spinel refractory material. (3) the blank obtained in step (2) is sintered at 1200°C for 10 h to obtain a magnesium-manganese-aluminum composite spinel refractory material.

[0055] Comparative Example 1 On the basis of Example 1, the additive is omitted, and the mass of calcium hexaluminate is set to 21 parts, and other conditions remain unchanged.

[0056] Comparative Example 2 On the basis of Example 1, the calcium hexaluminate is omitted, and the mass of the additive is set to 21 parts, and other conditions remain unchanged.

[0057] Comparative Example 3 Conventional ordinary cement kiln brick The magnesium-manganese-aluminum composite spinel refractory materials prepared in Example 1 and Comparative Examples 1-3 are subjected to performance testing, and the results are shown in Table 1.

[0058] Table 1 Performance data of the magnesium-manganese-aluminum composite spinel refractory materials prepared in Example 1 and Comparative Examples 1-3

[0059] In Table 1, the greater the bulk density, the lower the apparent porosity, the greater the cold crushing strength, the lower the thermal conductivity, the smaller the kiln heat loss, the lower the corrosion resistance value, the smaller the amount of erosion loss, the better the corrosion resistance, and the greater the adhesion strength value of the kiln skin, the better the kiln skin performance.

[0060] It can be seen from Table 1 that the additive and calcium hexaluminate in the application can synergistically reduce the thermal conductivity, and omitting the additive or calcium hexaluminate can reduce the thermal conductivity.

[0061] Example 2 On the basis of Example 1, the mass ratio of nano-zirconium oxide and nano-titanium oxide is set to 1:1, and other conditions remain unchanged.

[0062] Example 3 On the basis of Example 1, the mass ratio of nano-zirconium oxide and nano-titanium oxide is set to 1:3, and other conditions remain unchanged.

[0063] Example 4 On the basis of Example 1, the mass ratio of nano-zirconium oxide and nano-titanium oxide is set to 1:4, and other conditions remain unchanged.

[0064] Example 5 On the basis of Example 1, the mass ratio of nano-zirconium oxide and nano-titanium oxide is set to 1:5, and other conditions remain unchanged.

[0065] The magnesium-manganese-aluminum composite spinel refractory materials prepared in Examples 1-5 are subjected to performance testing, and the results are shown in Table 2, and the testing standards are the same as those in Table 1.

[0066] Table 2 Performance data of magnesium-manganese-aluminum composite spinel refractory materials prepared in Examples 1-5

[0067] Example 6 On the basis of Example 1, the mass fraction of calcium hexaluminate is set to 10 parts, i.e., the mass ratio of the additive and calcium hexaluminate is 1:10, and other conditions remain unchanged.

[0068] Example 7 On the basis of Example 1, the mass fraction of calcium hexaluminate is set to 15 parts, i.e., the mass ratio of the additive and calcium hexaluminate is 1:15, and other conditions remain unchanged.

[0069] Example 8 On the basis of Example 1, the mass fraction of calcium hexaluminate is set to 16 parts, i.e., the mass ratio of the additive and calcium hexaluminate is 1:16, and other conditions remain unchanged.

[0070] The magnesium-manganese-aluminum composite spinel refractory materials prepared in Examples 1 and Examples 6-8 are subjected to performance testing, and the results are shown in Table 3, and the testing standards are the same as those in Table 1.

[0071] Table 3 Performance data of magnesium-manganese-aluminum composite spinel refractory materials prepared in Examples 1 and Examples 6-8

[0072] Example 9 A magnesium-manganese-aluminum composite spinel refractory is prepared from raw materials in the following mass fractions: 120 parts of magnesite, 1 part of hercynite, 5 parts of α-Al2O3 micro powder, 0.1 part of manganese dioxide powder, 2 parts of manganese powder, 1 part of binder, 0.5 part of additive, 10 parts of calcium hexaluminate, and 15 parts of fiber; The magnesite is magnesite particles and magnesite fine powder; the particle size of the magnesite particles is 3-5 mm; the particle size of the magnesite fine powder is 0.063 mm or less; and the mass ratio of the magnesite particles to the magnesite fine powder is 5:1; The magnesite is electrically fused magnesite; the mass percentage content of MgO in the magnesite is 96%; The particle size of the hercynite is 1-3 mm; The chemical composition of the hercynite is, in mass percentage, Fe2O340.22%, SiO21.32%, Al2O355.81%, and CaO 2.65%; The particle size of the α-Al2O3 micro powder is 500 mesh; The particle size of the manganese dioxide powder is 400 mesh; The particle size of the manganese powder is 300 mesh; The binder is a calcium lignosulfonate solution, and the concentration of the calcium lignosulfonate solution is 1.23 g / mL; The additive is nano-zirconium oxide and nano-titanium oxide; the mass ratio of the nano-zirconium oxide to the nano-titanium oxide is 1:3; The D50 of the additive is 50 nm; 50 The D50 of the additive is 50 nm; The content of CaO in the calcium hexaluminate is 8 wt%, and the sphericity is 0.8; The particle size of the calcium hexaluminate is 0.1 mm; The fiber is titanium dioxide-coated aluminum silicate fiber, and the preparation method is as follows: 0.05 L of tetrabutyl titanate is added to 30 L of anhydrous ethanol and dispersed uniformly, then 1 kg of aluminum silicate fiber is added and mixed uniformly, and then the solvent is evaporated to obtain the fiber; wherein the Al2O3 content in the aluminum silicate fiber is 65.07 wt%, the SiO2 content is 34.13 wt%, the diameter is 3 μm, and the length is 3 mm; The mass ratio of the additive to the calcium hexaluminate is 1:20; The preparation method of the magnesium-manganese-aluminum composite spinel refractory is the following steps: (1) mixing magnesite, hercynite, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, binder, additive, calcium hexaluminate, and fiber to obtain a mixture; (2) The mixture obtained in step (1) is shaped under 12 kN / cm 2 at 150℃ for 50h to obtain a blank; (3) The blank obtained in step (2) is sintered at 1300℃ for 8h to obtain a magnesium-manganese-aluminum composite spinel refractory material.

[0073] Example 10 A magnesium-manganese-aluminum composite spinel refractory material is prepared from the following raw materials in mass fraction: 80 parts of magnesite, 10 parts of hercynite, 3 parts of α-Al2O3 micro powder, 1 part of manganese dioxide powder, 1 part of manganese powder, 2 parts of binder, 0.5 parts of additive, 10 parts of calcium hexaluminate, and 8 parts of fiber; The magnesite is magnesite particles and magnesite fine powder; the particle size of the magnesite particles is 3-5mm; the particle size of the magnesite fine powder is 0.063mm or less; and the mass ratio of the magnesite particles to the magnesite fine powder is 3:1; The magnesite is electrically fused magnesite; the mass percentage content of MgO in the magnesite is 96%; The particle size of the hercynite is 1-3mm; The chemical composition of the hercynite is Fe2O340.22%, SiO21.32%, Al2O355.81%, and CaO 2.65% in mass percentage; The particle size of the α-Al2O3 micro powder is 500 mesh; The particle size of the manganese dioxide powder is 400 mesh; The particle size of the manganese powder is 300 mesh; The binder is a calcium lignosulfonate solution, and the concentration of the calcium lignosulfonate solution is 1.23g / mL; The additive is nano-zirconium oxide and nano-titanium oxide; the mass ratio of the nano-zirconium oxide to the nano-titanium oxide is 1:4; The D 50 The particle size is 50nm; The content of CaO in the calcium hexaluminate is 8wt%, and the sphericity is 0.8; The particle size of the calcium hexaluminate is 0.1mm; The fiber is titanium dioxide coated aluminum silicate fiber, and the preparation method is as follows: 0.05L tetrabutyl titanate is added into 30L anhydrous ethanol and dispersed uniformly, then 1kg aluminum silicate fiber is added and mixed uniformly, and then the solvent is evaporated to obtain the fiber; wherein, the content of Al2O3 in the aluminum silicate fiber is 65.07wt%, the content of SiO2 is 34.13wt%, the diameter is 3μm, and the length is 3mm; The mass ratio of the additive to the calcium hexaluminate is 1:20; The preparation method of the magnesium-manganese-aluminum composite spinel refractory material comprises the following steps: (1) mixing magnesia, iron-aluminum spinel, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, a binder, an additive, calcium hexaluminate and fibers to obtain a mixture; (2) molding the mixture obtained in step (1) under a pressure of 15 kN / cm2, and then drying the mixture at 150 ℃ for 50 h to obtain a green body; 2 (3) sintering the green body obtained in step (2) at 1100 ℃ for 12 h to obtain the magnesium-manganese-aluminum composite spinel refractory material. (3) sintering the green body obtained in step (2) at 1100 ℃ for 12 h to obtain the magnesium-manganese-aluminum composite spinel refractory material.

[0074] The magnesium-manganese-aluminum composite spinel refractory materials prepared in Example 1 and Examples 9-10 are subjected to performance testing, and the results are shown in Table 4, wherein the testing standards are the same as those in Table 1.

[0075] Table 4 Performance data of the magnesium-manganese-aluminum composite spinel refractory materials prepared in Example 1 and Examples 9-10

[0076] As can be seen from the above examples and comparative examples, the magnesium-manganese-aluminum composite spinel refractory material provided by the present application has excellent strength, hanging kiln skin performance, corrosion resistance and low thermal conductivity.

[0077] The above description is only preferred embodiments of the present application, and it should be pointed out that, for ordinary skilled in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, and these improvements and refinements should be considered as the protection scope of the present application.

Claims

1. A magnesium-manganese-aluminum composite spinel refractory material, characterized in that, It is prepared from raw materials comprising the following parts by mass: Magnesia 40-120 parts, iron-aluminum spinel 1-20 parts, α-Al2O3 micro powder 1-5 parts, manganese dioxide powder 0.1-2 parts, manganese powder 0.1-2 parts, binder 1-5 parts, additives 0.1-1 parts, calcium hexaaluminate 10-20 parts, and fiber 5-15 parts; The fiber is titanium dioxide coated aluminum silicate fiber; The additives are nano-zirconia and nano-titanium oxide.

2. The magnesium-manganese-aluminum composite spinel refractory material according to claim 1, characterized in that, It is prepared from raw materials comprising the following mass percentages: The ingredients are: 50-100 parts magnesia, 5-15 parts iron-aluminum spinel, 2-4 parts α-Al2O3 micro powder, 0.5-1.5 parts manganese dioxide powder, 0.5-1.5 parts manganese powder, 2-4 parts binder, 0.2-0.9 parts additives, 12-18 parts calcium hexaaluminate, and 8-12 parts fiber.

3. The magnesium-manganese-aluminum composite spinel refractory material according to claim 1 or 2, characterized in that, The mass ratio of nano-zirconia to nano-titanium oxide is 1:(1~5).

4. The magnesium-manganese-aluminum composite spinel refractory material according to claim 1 or 2, characterized in that, The particle size of the α-Al2O3 micro powder is 400~600 mesh.

5. The magnesium-manganese-aluminum composite spinel refractory material according to claim 1 or 2, characterized in that, The particle size of the manganese dioxide powder is 300-500 mesh.

6. The magnesium-manganese-aluminum composite spinel refractory material according to claim 1 or 2, characterized in that, The mass ratio of the additive to calcium hexaaluminate is 1:(10~20).

7. The magnesium-manganese-aluminum composite spinel refractory material according to claim 6, characterized in that, The mass ratio of the additive to calcium hexaaluminate is 1:(14~16).

8. A method for preparing the magnesium-manganese-aluminum composite spinel refractory material according to any one of claims 1 to 7, comprising the following steps: (1) Mix magnesia, iron-aluminum spinel, α-Al2O3 micro powder, manganese dioxide powder, manganese powder, binder, additives, calcium hexaaluminate and fiber to obtain a mixture; (2) The mixture obtained in step (1) is shaped to obtain a blank; (3) The billet obtained in step (2) is sintered to obtain magnesium manganese aluminum composite spinel refractory material.

9. The preparation method according to claim 8, characterized in that, The forming pressure in step (2) is 10~15kN / cm. 2 .

10. The preparation method according to claim 8, characterized in that, The sintering temperature in step (3) is 1000~1300℃, and the sintering time is 5~12h.

Citation Information

Patent Citations

  • Refractory castable for ladles

    CN104311069A

  • Magnesium aluminate spinel refractory material containing manganese and preparing method thereof

    CN105777151A

  • Magnesium-manganese spinel refractory material as well as preparation method and application thereof

    CN113024228A

  • Refractory material for incineration sodium chloride high-salt rotary kiln

    CN115231935A

  • Refractory material with function of cleaning molten steel, preparation method therefor and use thereof

    US20240261851A1